What Old-School Economics Doesn’t Get About Democracy - Coy, Peter (NY Times, 2023)
Danielle Allen grew up, in her own words, “in an opinionated, fractious, loving family.” Her father, “lean and bald,” was a rare Black Reagan Republican. Her aunt Roslyn, “lesbian and built like a Mack truck, with a huge belly laugh,” was in the Peace and Freedom Party. They debated endlessly but respectfully. So wrote Allen in “Justice by Means of Democracy,” an important book that came out this year. Allen wrote that she took a little from her right-leaning dad and a little from her left-leaning aunt for the book. “A bit of market, a bit of public sector, civic virtue and room for experimentalism,” she wrote in the acknowledgments. Allen is a public intellectual. She has written, edited or contributed to 13 books. She’s a contributing columnist at The Washington Post. She has doctorates in both government and classics. She is the director of the Safra Center for Ethics at Harvard University. She was featured on Ezra Klein’s podcast in April. Oh, and she ran for governor of Massachusetts in the 2022 election, dropping out early last year. “Justice by Means of Democracy” is clearly special to her, though. When the first copy from the publisher was delivered to her doorstep in March, she tweeted, “A small green volume, a lifetime of work.”